Update on the correlation of the highest energy cosmic rays with nearby extragalactic matter - Badagnani, Daniel Omar (2010)
Data collected by the Pierre Auger Observatory through 31 August 2007 showed evidence for anisotropy in the arrival directions of cosmic rays above the Greisen–Zatsepin–Kuz’min energy threshold, 6 x 1019 eV. The anisotropy was measured by the fraction of arrival directions that are less than 3.1º from the position of an active galactic nucleus within 75 Mpc (using the Véron-Cetty and Véron 12th catalog). An updated measurement of this fraction is reported here using the arrival directions of cosmic rays recorded above the same energy threshold through 31 December 2009. The number of arrival directions has increased from 27 to 69, allowing a more precise measurement. The correlating fraction is (38+7-6)%, compared with 21% expected for isotropic cosmic rays. This is down from the early estimate of (69+11-13)%. The enlarged set of arrival directions is examined also in relation to other populations of nearby extragalactic objects: galaxies in the 2 Microns All Sky Survey and active galactic nuclei detected in hard X-rays by the Swift Burst Alert Telescope. A celestial region around the position of the radiogalaxy Cen A has the largest excess of arrival directions relative to isotropic expectations. The 2-point autocorrelation function is shown for the enlarged set of arrival directions and compared to the isotropic expectation.